The impact of COVID-19 and the confinement on the secondary level students of the Eastern region of Morocco - Hind Moumni; Fatima Elghazouani (Indian Journal of Psychiatry)
Context: In March 2020, Morocco announced the first COVID-19 case and implemented preventive measures, including home confinement. Aims: Monitoring the psychological effects and prevalence among high- and middle-school students. Settings and Design: This study is cross-sectional, carried online. Methods and Materials: The survey was conducted by publishing an online questionnaire between May 14, 2020 and June 14, 2020, which included inquiries about socio-demographic data, the conditions of home confinement, activities carried out during confinement, and medical history and sleep patterns. To assess depressive disorder, anxiety disorders, and stress, the survey employed the “DSRS-c,” “SCARED,” and “PSS10” scales, respectively. Statistical Analysis Used: Data were received on Google forms coded by Excel 2010 and analyzed by IBM SPSS Statistics 22. Results: Out of the 689 participants, 73.7% were females; the mean age was 16.08 years (standard deviation 1.48). 94.8% of subjects reported changes in sleep habits, and 41.4% of adolescents had high levels of depressive symptoms, while 50.7% had high levels of anxiety symptoms. Several factors were significantly associated with anxiety and depressive symptoms, including being a girl (P = 0.000), being a high-school student (P = 0.011), economic struggles during the pandemic (P = 0.003), doubting the necessity of home confinement (P = 0.000), spending over 3 hours a day on social networks and video games (P = 0.000), dropping out of remote learning (P = 0.000), having a psychiatric history (P = 0.000), having chronic illnesses in the family (P = 0.002), and changes in sleep habits (P = 0.000). Conclusions: The study found high prevalence of depression, anxiety, and stress symptoms among students during the pandemic, emphasizing the need for mental health awareness and support.